Test.retest reliability of the power push-up test in adolescent swimmers: force plate-derived parameters` reliability of power push-up test in adolescent swimmers - Öztürk, F.; Ünver, E.; Özçadirci, A.; Cinemre, S. A.; Kinikli, G. I. (Sport Sciences for Health, 2024)
Purpose The power push-up test can reveal significant differences in evaluating upper extremity strength. The aim of this study was to investigate the test-retest reliability of the parameters produced from the force platform of the power push-up test in young swimmers.